MEMBONGKAR SISI GELAP FINTECH PEER-TO-PEER LENDING (PINJAMAN ONLINE) PADA MAHASISWA DI YOGYAKARTA - Hidayah, Ahmad (Journal of Humanity Studies, 2022)
This study aims to discuss dismantling the dark side of fintech peer-to-peer lending (online lending) to college students in Yogyakarta. This study uses qualitative research methods and was conducted in the city of Yogyakarta. The results of this study state that the reason why college students in Yogyakarta City use and borrow money at illegal peer-to-peer  lending fintech (online lending) is the ease of registration and disbursement of funds as well as their hedonism needs. After all, they have to accept how the dark side of fintech peer-to-peer  lending (online lending) is illegal which is so detrimental. Therefore, it is necessary to inculcate the value of financial literacy from an early age therefore that this does not happen again.